Clostridium beijerinckii strain degeneration is driven by the loss of Spo0A activity - Humphreys, Jonathan R.; Debebe, Bisrat J.; Diggle, Stephen P.; Winzer, Klaus (Frontiers in Microbiology, 2023)
Solventogenic clostridia represent a diverse group of anaerobic, spore-forming bacteria capable of producing acetone, butanol and ethanol through their unique biphasic metabolism. An intrinsic problem with these organisms however is their tendency to degenerate when repeatedly subcultured or when grown continuously. This phenomenon sees cells lose their ability to produce solvents and spores, posing a significant problem for industrial applications. To investigate the mechanistic and evolutionary basis of degeneration we combined comparative genomics, ultra-deep sequencing, and concepts of sociomicrobiology using Clostridium beijerinckii NCIMB 8052 as our model organism. These approaches revealed spo0A, the master regulator gene involved in spore and solvent formation, to be key to the degeneration process in this strain. Comparative genomics of 71 degenerate variants revealed four distinct hotspot regions that contained considerably more mutations than the rest of the genome. These included spo0A as well as genes suspected to regulate its expression and activity. Ultra-deep sequencing of populations during the subculturing process showed transient increases in mutations we believe linked to the spo0A network, however, these were ultimately dominated by mutations in the master regulator itself. Through frequency-dependent fitness assays, we found that spo0A mutants gained a fitness advantage, relative to the wild type, presumably allowing for propagation throughout the culture. Combined, our data provides new insights into the phenomenon of clostridial strain degeneration and the C. beijerinckii NCIMB 8052 solvent and spore regulation network.